(untitled) (Cadernos de Sociomuseologia, 2022)
The research explores museological actions from 2011 to 2019 at the Memory Point in the periphery town known as Estrutural, 16 kilometers from the capital of Brazil, Brasilia. The founding of Estrutural in the 1960s originated from the activities of selective refuse collectors who settled around the dump. In the 1990s, Estrutural suffered huge irregular population density, which stimulated high indices of social and environmental crime, and the loss of biophilic references. The Memory Point has conducted numerous museum actions through inventories, exhibitions, cultural action and participatory conservation since its foundation This was encouraged by the Brazilian Museum Institute and community initiative for remembrance and social museology. Based on biophilic concepts, these processes were analyzed to verify if there were biophilic references in the museum actions that could stimulate self-creation and solidarity. The research methodology is qualitative, integrating action and research, which advocates dialogue between participants in order to encourage protagonism in actions and decisions. The results confirmed the presence of Biophilic Museology, with museological practices abundant in vitality, creation and cooperation, and a strong link with preservation issues. Key words: Social Museology; Sociomuseology; Memory Point; Biophilia; Participatory Conservation.